2012
DOI: 10.1002/jwmg.436
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering sparrow use of field borders planted as beneficial insect habitat

Abstract: Field borders are an effective conservation strategy for providing habitat to overwintering sparrows, and may be a venue through which beneficial insect populations are promoted. However, traditional fallow field borders lack sufficient pollen and nectar sources required to sustain beneficial insect populations; therefore, borders planted to a mix of native prairie flowers and grasses may be needed if increases in beneficial insect populations are desired. Although the value of fallow borders to birds has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For each survey, one experienced observer continuously walked along transects within each treatment and recorded the spatial location of each bird heard or seen on maps of treatments. For each detected bird, the observer recorded the following information: 1) discernable behavior (e.g., counter-singing, perching, foraging); 2) movement after initial detection (i.e., with directional arrows on maps), which aided in minimizing double-counting of individuals; 3) whether the bird was on the ground within ~1 m of a downed wood pile or windrow (herein “near pile”), within a downed wood pile or windrow (herein “in pile”), on branches protruding from a downed wood pile or windrow (herein “on branch of pile”), or among vegetation of any type (i.e., not in harvest residues or on bare ground); and 4) estimated distance to the nearest drainage ditch (i.e., edge) based on one of three classes: 1) 0–25 m; (2) 25–50 m; and (3) and ≥ 50 m. Because we surveyed breeding birds only within 25 m to either side of transect lines in relatively open areas consisting primarily of low-lying grasses and forbs and sparsely distributed shrubs, we assumed detection probability in treatments was near 100% [44, 45]. We did not handle birds during avian sampling; as such, our study was exempt from approval by the North Carolina State University Institutional Animal Care and Use Committee and federal/state agencies.…”
Section: Methodsmentioning
confidence: 99%
“…For each survey, one experienced observer continuously walked along transects within each treatment and recorded the spatial location of each bird heard or seen on maps of treatments. For each detected bird, the observer recorded the following information: 1) discernable behavior (e.g., counter-singing, perching, foraging); 2) movement after initial detection (i.e., with directional arrows on maps), which aided in minimizing double-counting of individuals; 3) whether the bird was on the ground within ~1 m of a downed wood pile or windrow (herein “near pile”), within a downed wood pile or windrow (herein “in pile”), on branches protruding from a downed wood pile or windrow (herein “on branch of pile”), or among vegetation of any type (i.e., not in harvest residues or on bare ground); and 4) estimated distance to the nearest drainage ditch (i.e., edge) based on one of three classes: 1) 0–25 m; (2) 25–50 m; and (3) and ≥ 50 m. Because we surveyed breeding birds only within 25 m to either side of transect lines in relatively open areas consisting primarily of low-lying grasses and forbs and sparsely distributed shrubs, we assumed detection probability in treatments was near 100% [44, 45]. We did not handle birds during avian sampling; as such, our study was exempt from approval by the North Carolina State University Institutional Animal Care and Use Committee and federal/state agencies.…”
Section: Methodsmentioning
confidence: 99%
“…Because we surveyed winter birds 25 m to either side of transect lines in relatively open areas consisting primarily of low-lying grasses (when vegetation was present), we assumed detection probability in treatments was near 100% (Diefenbach et al 2003, Plush et al 2013.…”
Section: Avian Sampling and Habitat Usementioning
confidence: 99%
“…The increased plant diversity is associated with increased invertebrate biomass ( Balzan, Bocci & Moonen, 2016;Hiron et al, 2015;Torretta & Poggio, 2013;Woodcock et al 2007) which may be useful food resources for birds ( Douglas, Vickery & Benton, 2009;Wiggers et al 2015;Ottens et al, 2014;Perkins et al, 2002;Woodcock et al, 2009). It is also reported that most of the field margins that were established and managed to promote beneficial insects are used by bird species as overwintering and refuge habitats (Plush et al, 2013). The optimal age and size of the field margin are reported to affect the richness and breeding densities of bird species where species richness and territory density increased up to the age of 4 to 6 years of the field margin, thereafter it started to decline (Zollinger et al, 2013).…”
Section: Increased Survival Of Bird Speciesmentioning
confidence: 99%